Dialética do castigo: histórias de um frade no Brasil holandês - Brito, Sylvia Brandão Ramalho de (2013)
This study focuses on the analysis of a narrative written during the dutch invasion to Brazil, the book entitled O Valeroso Lucideno e Triunfo da Liberdade. The work, published in 1648, in Lisbon, by the religious Manoel Calado, has João Fernandes Vieira, a "senhor de engenho" of Pernambuco, as financier and protagonist. The book, in which the central component was guided by providential history, had a strategic purpose. The work can be understood as a political project, guided by the marks of the historiography of the period, whose efforts lay in the discursive theory of "boa razão de Estado". In addition to understanding which were the justifications of "guerra da liberdade divina", our work aims to scrutinize the relationship between a panegyric written and aspirations of ennoblement. Finally, we look at the speech used by the religious in order to understand what ideals he stood for and meant to disclose in his writings.